A Factorial Survey Investigating the Effect of Disclosing Parental Intellectual Disability on Risk Assessments by Children's Social Workers in Child Safeguarding Scenarios. (30th June 2019) - Retzer, Ameeta; Kaye, Jane; Gray, Ron
Abstract: Literature suggests that, as parents, people with intellectual disabilities experience disproportionately high rates of child removal compared to other groups. A factorial survey of 191 children's social workers investigated the effect of disclosing parental intellectual disability (ID) upon risk assessments in a range of hypothetical child safeguarding scenarios. The case scenarios depicted a range of child safeguarding situations and parents' ID status was randomly included as an additional item of information. The data were fitted into a generalised ordinal logistic regression model. Findings indicate that when presented with scenarios considered to be less risky, the parental ID disclosure contributed significantly to a higher risk assessment score. However, when presented with scenarios that were considered more risky, the additional parental ID disclosure did not significantly contribute to a higher score. These findings indicate that the risk associated with parental ID is not fixed but relative to the situation in which it is encountered. The research concludes that in cases of low risk, the effect of parental ID is identified as a support need, whereas the lesser contribution of the disclosure to assessments of higher risk cases may indicate that parental ID is overlooked.